2014
DOI: 10.11648/j.avs.20140205.15
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Methods in the Profiling of Livestock Diseases in the Jos-Plateau, Nigeria

Abstract: This study was conducted with a view to collecting epidemiological data based on farmers' understanding of livestock diseases in the rural communities of Plateau State. In typical developing nations, animal diseases seem to pose the greatest challenge to human and animal health and welfare. Unfortunately, most of such nations rely so much on inefficient "top to bottom" disease surveillance and eradication policies, as such, negative impacts of diseases are common. Participatory disease surveillance recognizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It further elucidates the fact that ND outbreaks will directly affect most needed animal protein intake as well as settlement of emergency fees such as school fees in many rural communities in northeastern Nigeria. The results of matrix scoring (Table 2) showed that farmers usually recognize ND by nervous signs, whitish diarrhoea, high morbidity and mortality which agree with some established literatures [8] [10] [11]. In many literatures however, greenish diarrhoea especially in acute ND infections supersedes the white diarrhoea reported by farmers [10] [11].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It further elucidates the fact that ND outbreaks will directly affect most needed animal protein intake as well as settlement of emergency fees such as school fees in many rural communities in northeastern Nigeria. The results of matrix scoring (Table 2) showed that farmers usually recognize ND by nervous signs, whitish diarrhoea, high morbidity and mortality which agree with some established literatures [8] [10] [11]. In many literatures however, greenish diarrhoea especially in acute ND infections supersedes the white diarrhoea reported by farmers [10] [11].…”
Section: Discussionsupporting
confidence: 82%
“…This means that farmers may lack the ability to recognize acute ND that may not be associated with the normal nervous signs and high mortality and most especially may lack the ability to recognize HPAI therefore limiting their ability to report suspected cases. Matrix scoring further made it possible to evaluate certain disease syndromes like "makere (somnolence), fakat (massive death), and farin kasha (white diarrhea)" to mean ND as understood by the Hausas and this seems to agree with the clinical presentations of ND as existed in many scientific findings on ND [8] [10] [11]. The major limitations in the conduct of participatory research especially in the livestock subsector and particularly in Nigeria are willingness of target farmers to participate in the absence of incentives and also participants tend to look at the study from a political perspective.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The livestock sector is important to the national economy, contributing to both financial and nutritional needs of the country through meat, milk and hides (6–8% of GDP) [ 1 ]. Veterinary services in Nigeria fail to meet the animal health needs of Fulani who have poor access to veterinary products and services [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. Disease surveillance, extension practice and veterinary service delivery are affected by a range of structural issues in Nigeria ranging, from failings in logistics to a lack of engagement with end users.…”
Section: Introductionmentioning
confidence: 99%